(untitled) (Research, Society and Development, 2020)
Desmoplastic fibroma is a very rare benign osteogenic tumor composed of diffuse fibroblasts and abundant collagen fibers. It is locally aggressive and presents a high recurrence rate, so its treatment can be a challenge and several strategies have been described as a way to prevent its recurrence. Thus, the aim of this report was to present the clinical course and treatment of a patient diagnosed with desmoplastic fibroma in the left zygomatic arch region. A case of a 37-year-old patient, whose complaint was painless volume increase in the face with approximately six months of evolution, was described. The physical examination showed a firm, solid and well-delimited mass in the temporal region of the left zygomatic arch, which was submitted to surgical excision. Histological findings of the lesion included fusiform cells involved in diffuse interstitial collagen deposition with absence of superficial mucous lining, compatible with desmoplastic fibroma. The patient is 2 years and 6 months postoperatively, showing no signs of recurrence of the lesion.